Knowledge of nurses towards dengue fever in a tertiary care teaching hospital in Nepal - Valarmathi, S; Parajulee, S (Journal of College of Medical Sciences-Nepal, 2014)
Background: Nurses are important health care professionals and should have wide knowledge about common diseases especially infectious diseases like dengue. Dengue is associated with shock and can lead to death. Aim: To assess the knowledge of nurses regarding dengue fever and to study the association between the demographic variables. Setting and design: A cross sectional study was conducted at the College of Medical Sciences-Teaching Hospital, Nepal among the nurses during December, 2010. Study tool: Semi structured question was prepared to assess the knowledge of nurses in which there was objective question and Yes or No type questionnaire. Statistical analysis: The filled questionnaires were collected and data were entered in Microsoft excel sheet and analyzed as per study objectives. Descriptive statistic was used to calculate the median (IQR) and non parametric tests (Kruskal Wallis test and Mann Whitney test) to compare the total scores with demographic profile of the subjects. Results: Of the study members 89% were from Proficiency Certificate level (PCL) background and the mean (IQR) age of the respondents was 21 years (20-22.75). Overall score of the nurses was 11 (9-13) with a maximum possible score of 17. There were no association between the respondents knowledge scores with age (p=0.14); educational qualifications (p=0.86); duration of experience (p=0.59); ward (p=0.28). Conclusion: The study findings report a low knowledge among the nursing practitioners on dengue fever and its complications and their knowledge did not have any association with their demographic variables. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 7-13 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9667